فثلساين ترهادف خابران دالم فغوروسن كوتيفن زكاة دان أئيهنث دمجليس أئام اسلام تيئ ولاية سلاتن تايلند: แนวทางการแก้ไขอุปสรรคความท้าทายการจัดเก็บและแจกจ่ายซะกาตของคณะกรรมการอิสลามในสามจังหวัดชายแดนภาคใต้ของประเทศไทย - สนิ, คอลิด (Al-HIKMAH Journal, 2021)
Abstract Charity (Zakat) is one of Islamic pillars that all Muslims are obligated to practice which has the definitive evidence in its legislation. It is, moreover, the economic development stimulator. So the good management in charity is counted important for the growth of the economy and people being, especially in three southern border provinces of Thailand. This research was aimed to study charity collecting and distributing obstacles, focusing on the challenges faced by the charity officials of Islamic Councils at three southern provinces of Thailand, as well as suggesting some solving ways. The study used two main sources; those were documentary data and field data. The sample of population of the study were 99 people, consisting of three southern province’s Islamic Council officials, Charity officials appointed by the Islamic councils, charity givers, charity receivers and general people. The collected data was then analyzed by inductive, deductive and comparative methods. The researcher also has suggested solving ways as following: 1.Holding seminars about charity. 2. Preparing lessons of charity and distribute them to the Muslim community. 3. Making the registration of Muslim population for Three Southern provinces. 4. Conducting research about charity. 5. Setting rules and policy of charity, 6. Assigning a roles to charity institution, 7. Making people believe and confident in charity institutions. 8. Visiting and exchanging charity experiences with successful charity institutes 9.Conducting reviving plan for charity funds.